GroRecipe: a mobile application for a meal planner - Rosman, Muhammad Rusydi; Mohd Rum, Siti Nurulain; Mohd Ariffin, Noor Afiza; Asmawi, Aziah; Husin, Nor Azura (Research Malysia Publications, 2019)
Today, the advances in technology have led to the use of smart phones in health practices. In this paper, an android-based mobile application named GroRecipe, a meal planner system is developed. The main objective of developing GroRecipe is to encourage the practice of a healthy lifestyle. This can be achieved by making the meal planning effortless, healthy and tasty. GroRecipe can also speed up the meal preparation process by helping the user to estimate the amount of ingredients needed of a recipe based on the number of serving size per meal. It also provides the feature to auto generate the grocery lists, making the grocery purchasing decisions easier. Users can also enjoy using GroRecipe by sharing their recipe with others and rating the recipes posted by others. This can help to improve the quality of cooking in terms of its taste with healthy ingredients. The technologies used to develop the GroRecipe are Java, as the programming language, Firebase cloud, as the database and Android Studio as the IDE.